2012
DOI: 10.3138/ptc.2010-42
|View full text |Cite
|
Sign up to set email alerts
|

The Path to Self-Management: A Qualitative Study Involving Older People with Multiple Sclerosis

Abstract: Purpose: This qualitative study sought to explore older people's experience of ageing with multiple sclerosis (MS) and to describe the natural history of self-management from their points of view. Methods: Eighteen people over age 55 and living with MS for at least 20 years were recruited from an MS clinic and rehabilitation outpatient records. Interviews (60-80 min), using open-ended questions, explored participants' lifelong experiences of MS. Following interview transcription, data were coded and analyzed; … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
82
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(87 citation statements)
references
References 29 publications
(39 reference statements)
3
82
0
2
Order By: Relevance
“…More importantly, a number of incapacitating MS symptoms such as bowel and bladder incontinence and pain impede employment and social participation. 27 Thus, items are required to more fully assess the many complex dimensions of MS selfmanagement.…”
Section: Discussionmentioning
confidence: 99%
“…More importantly, a number of incapacitating MS symptoms such as bowel and bladder incontinence and pain impede employment and social participation. 27 Thus, items are required to more fully assess the many complex dimensions of MS selfmanagement.…”
Section: Discussionmentioning
confidence: 99%
“…In order to describe healthy aging from the perspective of the older person with MS, researchers interviewed 18 people who were 55 years of age and older with symptoms for 20 or more years. 54,55 Analysis of key themes emerging from the data showed that older people with MS highly valued four major factors that they felt contributed to health and life satisfaction as they aged 54 : work and social engagement, effective and accessible health care, healthy lifestyle habits, and maintaining independence at home.…”
Section: Research On Aging and Older Adults With Multiple Sclerosismentioning
confidence: 99%
“…Using a qualitative research approach, researchers found that study participants, despite reporting problems with balance and falls, did not wish to use walking aids or wheelchairs. 55 They explained that using these devices had two drawbacks from their points of view: first, canes, walkers, and wheelchairs were perceived as clear signs of disability that attracted sometimes unwanted attention from others; second, they considered the use of devices to be a sign of "giving up" or accommodating to MS. Participants felt that by using mobility aids, they would sacrifice potentially beneficial exercise effects of unaided (but often unsteady) walking on their balance and leg strength.…”
Section: Promoting Physical Activity For Adults With Ms: What We Knowmentioning
confidence: 99%
See 1 more Smart Citation
“…If the latter is the case, this would lend support to Ploughman and colleagues' hypothesis that over time, and after years of problem-solving and positive health care interactions, people with MS effectively apply self-management skills, including the attitudes and behaviours required to optimize emotional, social, and physical wellness. 1 For clinicians, assisting patients in this constructive journey to self-management is a positive shift in the therapeutic approach to patients with MS. As Ploughman and colleagues suggest, our role as physiotherapists is to expedite this process, earlier in the disease course if possible. 1 Life with MS is one example of a selfmanagement programme that promotes adjustment to MS and the skills required to live with this chronic, disabling disease.…”
mentioning
confidence: 99%